A Modelling Framework of Sustainable Supply Chain Management for Organic Vegetables in Rural Area with Narrow Land: An Action Research in Indonesia - Margunani Margunani; Inaya Sari Melati; Etty Soesilowati (International Journal of Supply Chain Management, 2018)
As a developing country, food security is still an important issue in Indonesia. The increase in demand for organic vegetables products over the last couple of decades has created one of the fastest growing sectors within the fresh produce industry. The low productivity of housewives in villages and their lax spare time are well positioned to take advantage of existing sustainable and profitable opportunities, specifically in organic vegetables production even they only have narrow land. This study aims: (1) to demonstrate the hidden potency of rural housewives community to apply modern technology in cultivating organic vegetables for narrow land, and (2) to develop supply chain management modelling tools of organic vegetables for supporting food security system in rural area. The subjects of this study are housewives in rural area of Semarang City in Province Central Java, Indonesia. By employing an exploratory sequential mixed methods research design, this studys results show that the proposed supply chain management model is proven as an appropriate model to secure supply chain of organic vegetables in rural area. Using this model, organic vegetables cultivation sustainably maintains the familys food self-sufficiency and lead to semi-commercial needs of the surrounding communities.